Boycotts and brand perception of mineral water affecting generation Z Muslim purchases - Khasanah, Miftakhul; Kaha, M. Radjasa Sing Agul Kusuma (Faculty of Business & Economics, Universitas Islam Indonesia, 2024)
Purpose – This study aims to identify the determinants of purchasing decisions for bottled mineral water among generation Z Muslims in Indonesia, particularly in light of product boycotts. Methodology – The sample consisted of 189 respondents, with the criteria being generation Z Muslims in Indonesia who have made purchases of mineral water after the boycott actions against several mineral water brands in Indonesia due to the conflict between Israel and Palestine. Findings – Purchasing decisions for mineral water by generation Z Muslims in Indonesia are influenced by halal labeling, brand perception, and promotions related to social and ethical issues, including boycotts against certain brands. The analysis results indicate that consumers not only consider the quality and halal aspects of the product, but also actively respond to the values promoted by the brand, especially in relation to controversies involving brand affiliations with entities that do not align with Islamic principles. Implications – The mineral water industry needs to manage brand image and marketing strategies by considering the cultural and social values of consumers, particularly generation Z Muslims in Indonesia. With the growing awareness of ethical and political issues, the industry must ensure that its products meet quality and halal standards, as well as avoid associations with controversies that could trigger boycotts.Originality – This study integrates social and ethical aspects, such as responses to boycott actions and halal awareness, into consumer behavior analysis, providing a new perspective on understanding market dynamics influenced by cultural values and religious beliefs.